Clinical evaluation of osteocalcin in chronic hemodialysis patients - Nishio, S (Hinyokika kiyo. Acta urologica Japonica, 1989)
Serum level of osteocalcin was measured by radioimmunoassay in 52 patients with chronic renal failure and 92 control subjects. The patients were treated by usual hemodialysis over a 3-month period. The osteocalcin level of the patients was significantly higher than that of the control subjects, but the patients with diabetic nephropathy had a lower osteocalcin level than the patients with non-diabetic nephropathy. There was a significant correlation between serum osteocalcin level and alkaline phosphatase or PTH level. On the other hand, there was no relationship between serum osteocalcin level and various parameters such as bone mineral contents, and bone cortex volume measured by the microdensitometry method. Hemodialysis affected the serum osteocalcin level. The clinical value of osteocalcin as a parameter of bone formation in chronic hemodialysis patients was discussed